Association of Coronary Artery Calcification with MDA-LDL-C/LDL-C and Urinary 8-Isoprostane in Japanese Patients with Type 2 Diabetes - Nagasawa, Kan; Kajiwara, Takashi; Takahashi, Kazuma; Takahashi, Yoshihiko; Takebe, Noriko; Taneichi, Haruhito; Sasai, Takayoshi; Oda, Tomoyasu; Matsui, Mizue; Satoh, Jo; Nakagawa, Riyuki; Ono, Mitsutaka; et al. (Internal Medicine, 2014)
Objective Oxidative stress has been implicated in the development of coronary artery calcification (CAC). However, there are few reports on this issue in Japanese patients with diabetes. In this study, we examined the association of the CAC score (CACS) with oxidative stress markers. Methods The study subjects were 163 Japanese patients with type 2 diabetes (75 men and 88 women). The CACS (Agatston unit: AU) was measured by multi-detector computed tomography (MDCT), and the oxidative stress markers, such as the urinary 8-isoprostane and 8-hydroxydeoxyguanosine (8-OHdG) and serum malondialdehyde (MDA)-LDL cholesterol were measured. The relationships between CACS and oxidative stress markers were statistically analyzed. Results Compared with the CACS 0-400 AU group (n=132), the age, duration of diabetes, urinary 8-isoprostane levels, serum MDA-LDL-C/LDL-C and maximum intima media thickness (IMT) were higher, and body mass index and HbA1c level were lower, in the CACS >400 AU group (n=31). The multiple logistic regression analysis showed that a CAC >400 AU was independently associated with the urinary 8-isoprostane (>median) (OR=2.54, 95% CI=1.03-6.32, p=0.044), MDA-LDL-C/LDL-C (>median) (OR=2.62, 95% CI=1.07-6.40, p=0.035) and HbA1c (>median) (OR=0.32, CI=0.12-0.87, p<0.025). Focusing on oxidative stress, a higher MDA-LDL-C/LDL-C (p=0.026) and a higher urinary 8-isoprostane level (p=0.074) were associated with the CACS. Conclusion The CACS was found to be independently associated with the MDA-LDL-C/LDL-C and urinary 8-isoprostane levels in Japanese patients with type 2 diabetes.